THE ROLE OF SEMIOTICS IN MODERN LINGUISTICS - Ibrokhimova, Dilrabo; Komiljonova, Mavluda (GOLDEN BRAIN, 2024)
Semiotics, the study of signs and symbols and their use or interpretation, plays a significant role in modern linguistics. It bridges the gap between language as a system and its practical usage in diverse communication contexts. This article explores the fundamental principles of semiotics, its historical development, and its contribution to modern linguistic theories. By analyzing the interplay between signs, meanings, and cultural contexts, the article highlights how semiotics enriches linguistic research, enhances interdisciplinary approaches, and provides insights into the evolution of human communication.